Asuhan Keperawatan Ketidakefektifan Pola Nafas dengan Asma Bronkial di Ruang Lavender RSUD dr. R Goeteng Taroenadibrata Purbalingga: Nursing Care of Breathing Pattern Ineffectiveness with Bronchial Asthma in the Lavender Room of RSUD dr. R Goeteng Taroenadibrata Purbalingga - Pangestu, Ardyan Sigit; Tri Y, Danang; Putrianti, Dwi Puji (MPI Press, 2023)
Introduction: Bronchial asthma is a chronic inflammatory disorder in the respiratory tract that attacks the trachea and bronchi which are commonly found among the public. Factors that can trigger bronchial asthma attacks include allergy, gender, genetic or hereditary factors, respiratory tract infections, excessive exercise, cigarette smoke irritants, weather changes, and environmental factors. Narrowing of the airway can cause wheezing, coughing, or shortness of breath. Recurrence of asthma can cause the sufferer to have difficulty breathing so that the incoming air is reduced. Objectives: The purpose of this case study is to describe the nursing care ineffectiveness of breath patterns in Mr. A with bronchial asthma. Method: Researchers use the case study method with the stages of the nursing process including assessment, formulation of nursing diagnoses, planning, implementation, evaluation, and documentation. Nursing care is given for 3 days using nebulizer therapy. Data collection is carried out by interview, observation, and documentation methods. Result: The results were obtained by patients complaining of shortness of breath for 4 days and having a history of asthma. Physical examination obtained blood pressure 160/80 mmHg, temperature 36.3°C, pulse 89 x/min, SpO2 88%, RR 30 x/min, shallow breathing and additional breathing sounds (wheezing). Conclusion: The author performs airway nursing care for 3x24 hours with breathing monitors, teaches deep breath techniques, positions patients semi-fowler or as comfortably as possible, monitors oxygen status, monitors vital signs, and the administration of collaborative therapy administering bronchodilator nebulizers. The patient's problem is solved by the intervention.